Rediscovering Physical Collections through the Digital Archive: The Jesuit Libraries Provenance Project. Issue 4 (December 2016) - Roberts, Kyle B.
Historic library collections offer a rich and underexplored resource for teaching undergraduate and graduate students about new digital approaches, methodologies, and platforms. Their scope and scale can make them difficult to analyze in their physical form, but remediated onto a digital platform, they offer valuable insights into the process of archive creation and the importance of making their content available to audiences that cannot normally access it. The Jesuit Libraries Provenance Project (JLPP) was launched by students, faculty, and library professionals in 2014 to create an online archive of marks of ownership—bookplates, stamps, inscriptions—contained within books from the original library collection of St. Ignatius College, precursor to Loyola University Chicago. The project grew out of student work for a university museum exhibition commemorating the bi-centennial of the restoration of the Society of Jesus (more commonly known as the Jesuits). Utilizing the popular social media image-sharing site Flickr, the JLPP seeks to foster a participatory community of students, scholars, collectors, and the broader public interested in the history of early and modern Catholic print and the intellectual framework and approach of 19th-century Jesuit education. Initially intended to provide students with the chance to learn how to conceptualize, plan, and build a digital archive, the JLPP has proven equally effective for teaching about digital scholarship, shared authority, and, rather unexpectedly, about the materiality of collections in the digital age